An unusual cause of ventriculoperitoneal shunt infection. Issue 8 (August 2015) - Esmaeilzadeh, Majid; Islamian, Ariyan Pirayesh; Lang, Josef M.; Hornef, Mathias; Suerbaum, Sebastian; Krauss, Joachim K.
Abstract : ABSTRACT: Infection associated with ventriculoperitoneal (VP) shunt implantation can be a significant problem. VP shunt infection with Serratia marcescens, a gram-negative anaerobic rod, usually is related to underlying abdominal disease. This article describes treatment of two patients suffering from a VP shunt infection with S. marcescens without underlying abdominal disease.